Optical Spectroscopy of Li6Y(BO3)3 Single Crystals Doped with Dysprosium - Éva Tichy-Rács; Ivo Romet; László Kovács; Krisztián Lengyel; Gábor Corradi; Vitali Nagirnyi (Crystals, 2021)
The energy levels of Dy3+ ions have been determined in lithium yttrium borate (Li6Y(BO3)3) single crystals in a wide spectral range between 3000 and 40,000 cm−1 using optical absorption and luminescence spectroscopy, which also allow for an analysis of the ground state. The crystal field splittings of the 6H15/2 ground state and all excited states up to the 4F7/2 manifold were obtained at a low temperature, based on luminescence (T = 4.2–78 K) and absorption (T = 8–100 K) measurements, respectively. The numbers of experimentally observed Stark sublevels are in agreement with those expected theoretically for Dy3+ ions occupying a single low symmetry (C1) site.